Pengaruh Net Profit Margin, Return On Assets, Earning Price Ratio, dan Price Earning Ratio Terhadap Harga Saham (Studi Kasus Pada Hotel, Travel and Transportation Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Sudarsini, Denok (2016)
Research titled "Influence Of Net Profit Margin (NPM) , Return On Assets (ROA) , Earning Per Share (EPS), And Price Earning Ratio (PER) Of Stock Prices To Companies Hotel , Travel And Transportation Listed On Bursa Efek Indonesia The Period Starting From 2011 Until 2013" aims to understand independent variable influence NPM, ROA, EPS, and PER of stock exchange to companies hotel, travel and transportation at the bursa efek indonesia. Sample in research this is a company hotel, travel and transportation which consisted of 13 company which presents financial report a complete of 2011 until 2013. The method of analysis the data used in this research using test regression data panel with the methods fixed effect. The research results show that in test t variable ROA ,EPS ,and PER have had a positive impact significant impact on stock prices to companies hotel, travel and transportation. While variable NPM do not affect significant impact on stock prices. By the experiment F variable NPM, ROA, EPS, and PER with the same effect to share prices. Keyword : Net Profit Margin, Return On Assets, Earn